Multiplicative (Generalized) Reverse Derivations on Semiprime Ring (European Journal of Pure and Applied Mathematics, 2018)
Let R be a semiprime ring. A mapping F : R → R (not necessarily additive) is called a multiplicative (generalized) reverse derivation if there exists a map    d : R → R (not necessarily a derivation nor an additive map) such that F(xy) = F(y)x + yd(x) for all x, y є R. In this paper we investigate some identities involving multiplicative (generalized) reverse derivation and prove some theorems in which we characterize these mappings.
Keywords: Semiprime ring; Ideal; Multiplicative (generalized) reverse derivation.